2009
DOI: 10.1007/s11738-009-0377-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heavy metals on root growth and peroxidase activity in barley root tip

Abstract: In the present work, we investigated the alteration of oxidative and peroxidative activities of peroxidases (PODs) along the longitudinal root axis of barley seedlings during heavy metal (HM; e.g.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 47 publications
1
13
0
1
Order By: Relevance
“…'Virginia' agrees with other authors' results for different species (Kaplan et al, 1990;Wang et al, 2008;Olness et al, 2005;Potters et al, 2007). The increased thickness and shorter length of the roots are symptoms of vanadium toxicity (Morrell et al, 1986;Martín and Saco, 1995;Potters et al, 2007); this decrease in root growth may be due to an increase in wall lignification as a defence mechanism (Halusková et al, 2010). The symptoms and growth values obtained suggest than these vanadium doses, 40 μM and 80 μM, may be toxic for N. tabacum plants, and that the highest dose may be near the toxicity threshold.…”
Section: Discussionsupporting
confidence: 89%
“…'Virginia' agrees with other authors' results for different species (Kaplan et al, 1990;Wang et al, 2008;Olness et al, 2005;Potters et al, 2007). The increased thickness and shorter length of the roots are symptoms of vanadium toxicity (Morrell et al, 1986;Martín and Saco, 1995;Potters et al, 2007); this decrease in root growth may be due to an increase in wall lignification as a defence mechanism (Halusková et al, 2010). The symptoms and growth values obtained suggest than these vanadium doses, 40 μM and 80 μM, may be toxic for N. tabacum plants, and that the highest dose may be near the toxicity threshold.…”
Section: Discussionsupporting
confidence: 89%
“…Silicon supply slightly increased GPX activity at normal Mn, but significantly decreased its activity at excess Mn (Shi et al 2005). Analysis of the individual root segments of barley revealed that all of the analyzed metals (Cd, Cu, Hg, Ni, Pb) caused an increase of GPX activity, however to a different extent and spatial distribution (Halušková et al 2010). In the study published by Song et al (2011), activities of antioxidant enzymes (SOD, CAT and APX) were increased in Si supplied plants of both Zn-sensitive and Zn-resistant rice cultivars exposed to 2 mM of Zn, which confirms alleviative effects of Si in rice.…”
Section: Discussionmentioning
confidence: 96%
“…peroxidases, catalases, superoxide dismutases etc.] (Halušková et al 2010) and by accumulation of compounds that enhance chelatation or sequestration of metals (e.g. organic acids, phytochelatins (PCs) or metallothioneins) (Cobbett and Goldsbrough 2002).…”
Section: Introductionmentioning
confidence: 99%